Narodnostni vidiki parlamentarnih volitev na Madžarskem leta 2022 s posebnim ozirom na slovensko narodnost - Dobos, Balázs (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
The 2022 parliamentary elections in Hungary offered for the third time an opportunity for national minorities to elect their representative by casting a preferential vote for their Member of Parliament. However, the failure of the list of representatives of the most numerous ethnic group, the Roma, and the ruling of the European Court of Human Rights concerning the violation of multiple elements of the electoral system underscored the need for a comprehensive assessment of hitherto experience and for a reform of the preferential minority mandate and the institution of advocacy. This study aims to contribute to this process by examining the institutional framework and the electoral results, with a particular focus on the analysis of minority-related aspects of the last parliamentary elections and the situation of the Slovene national minority.
Keywords: ethnopolitical mobilisation; etnopolitična mobilizacija; European court of human rights; Evropsko sodišče za človekove pravice; Hungary; Madžarska; parlamentarno zastopstvo narodnosti; parliamentary representation of national minorities; Slovene minority (Hungary); Slovene minority advocate in the Hungarian parliament; slovenska manjšina (Madžarska); volilna udeležba; voter turnout; zagovornica Slovencev v madžarskem parlamentu